Pengaruh Takaran Aplikasi Pupuk Trichokompos Terhadap Pertumbuhan Dan Hasil Tanaman Kubis Bunga (Brassica Oleracea Var. Botrytis L) di Tanah Ultisol - Rizal, Ahmad; Langai, Bambang Fredrickus; Nisa, Chatimatun (Universitas Lambung Mangkurat, 2023)
This research aims to determine the effect and the best dose of trichocompost on the growth and yield of flower cabbage in ultisols. This research was conducted in July - October 2019 at the Mustika Griya Cantik complex B167, Cindai Alus Village, Banjar Regency, South Kalimantan Province. single factor completely randomized design, namely trichocompost fertilizer consisting of 7 levels of treatment repeated 4 times so that 28 experimental units were obtained and each experimental unit was repeated twice so that the total experiment was 56 units. The treatments used were k0: without trichocompost fertilizer, k1: trichocompost fertilizer 7.5t , k2: 15 t, k3: 22.5 t, k4: 30 t, k5: 37.5 t, k6: 45 t. The results of this study effect trichocompost on plant height at 28 days after planting, lots of leaves, flower emergence time, flower diameter And the best or dominant dose is more stable as seen from the results of the study, namely the dose of 37.5 t ha-1.